Investigation of Dielectric Response in a 22/0.4 kV Distribution Transformer: Effects of Moisture Content - Danaiwat Daengdee; Chanin Bunlaksananusorn; Dusit Suksawat; Komin Chumpiboon; Siwakorn Jeenmuang; Norasage Pattanadech (My University, 2024)
Transformers play a crucial role in power systems, ensuring efficient energy transmission and distribution. This research focuses on a 22/0.4 kV transformer decommissioned after over 20 years of service. The study involves draining the transformer oil completely and refilling it with oil characterized by known moisture content and breakdown voltage levels until reaching normal operating conditions. The objective is to study the effects of increased moisture content on the dielectric response within the actual structure of the transformer. Diagnostic measurement techniques, including Frequency Domain Spectroscopy (FDS) and Polarization Depolarization Current (PDC), are utilized to evaluate the insulation condition of the transformer. FDS provides information on the dielectric response over a wide frequency range, while PDC assesses the polarization and depolarization behavior of the insulation material. These techniques offer valuable information on the ageing and moisture content of the insulation. The experimental results will be presented and discussed in this paper.
Keywords: Power Transformer Diagnostics and Insulation; High voltage insulation and dielectric phenomena; Magnetic Properties and Applications